Effects of the Herbicide Metsulfuron-Methyl on a Plant Community, Including Seed Germination Success in the F1 Generation - Nelemans, J. Bas; van Wijngaarden, René P. A.; Roessink, Ivo; Arts, Gertie H. P. (Frontiers in Environmental Science, 2017)
A field trial was set up to simulate a field margin environment to analyze sub-lethal effects of the herbicide metsulfuron-methyl on several endpoints of non-target terrestrial plants (NTTPs). Both vegetative and reproductive endpoints were evaluated. The experiment was conducted in an experimentally established field strip with sown species. The treatments consisted of five dosages and a control: 0, 0.0097, 0.0193, 0.058, 0.174, and 0.348 gram active ingredient per hectare (g a.i./ha). The plant cover, number of (flowering) individuals per species and fruit collection were performed and estimated weekly for a period of 4 months. At the end of the growing season, the total dry biomass per species was obtained and the collected fruits were weighed, counted, and sieved to obtain the seeds. The seeds were counted and weighed as well, before they were used in a germination experiment to test the seed emergence of the F1 generation. The herbicide only affected the biomass of Matricaria recutita at the treatment levels tested (0.058 g a.i./ha and higher). Field dosages of 0.174 and 0.348 g a.i./ha differed significantly in the endpoint “plant cover” compared to lower dosages and controls. The F1 generations of Sinapis alba, Centaurea cyanus, and Phacelia tanacetifolia were particularly affected at field dosages of 0.0193 g a.i./ha and higher, showing significantly lower seed germination rates. This would imply that spray drift of metsulfuron-methyl might lead to shifts in species compositions and succession in vegetation in off-crop areas adjacent to arable fields. Conducting germination experiments is necessary to investigate a herbicide's effect on the full life cycle of plants.